Assessment Testing Can Be Used to Inform Policy Decisions : The Case of Jordan - Abdul-Hamid, Husein; Abu-Lebdeh, Khattab M.; Patrinos, Harry Anthony (2012)
Over the past two decades, the Jordanian education system has made significant advances. Net enrollment in basic education increased from 89 percent in 2000 to 97 percent in 2006. Transition rates to secondary education increased from 63 to 79 percent in the same period. At the same time, Jordan made significant gains on international surveys of student achievement, with a particularly impressive gain of almost 30 points on the science portion of the Third International Mathematics and Science Study. Changes in test scores over time are presented and analyzed using decomposition analysis. The trends are related to policy changes over time. It is argued that benchmarking education systems and constant feedback between researchers and policymakers contributed to this achievement.